Method for testing electrochemical corrosion performance of thick and thin WC enhanced 316L deposition sample

The deposition samples of coarse and fine WC/316L composite materials were prepared through laser melting deposition technology and electrochemical tests were carried out, which solved the problem of inaccurate evaluation of the electrochemical corrosion performance of the materials in the prior art, and achieved an accurate evaluation of the corrosion resistance of the materials. In particular, it was found that the fine WC/316L material showed the best corrosion resistance.

CN119555581AInactive Publication Date: 2025-03-04NANTONG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411870339.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively evaluate the electrochemical corrosion performance of thick and thin WC-enhanced 316L materials, resulting in inaccurate evaluation of corrosion resistance.

Method used

Different types of coarse and fine WC/316L composite deposition samples were prepared using laser melting deposition technology, and the three-electrode system was tested through an electrochemical workstation to measure the dynamic potential polarization curve and electrochemical impedance spectrum to obtain relevant corrosion performance parameters.

Benefits of technology

Through this method, the electrochemical corrosion performance of the thick and thin WC-enhanced 316L material can be accurately evaluated, and it was found that the fine WC/316L material showed the best corrosion resistance, with the maximum polarization resistance and total impedance value significantly higher than other materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119555581A_ABST
    Figure CN119555581A_ABST
Patent Text Reader

Abstract

The invention discloses a method for testing the electrochemical corrosion performance of a coarse and fine WC-enhanced 316L deposition sample, and relates to the technical field of laser melting deposition, and the method comprises the following steps: S1, uniformly mixing 316L powder and WC powder to obtain a coarse and fine WC / 316L composite material; s2, using laser melting deposition equipment to prepare different types of WC / 316L composite materials with different thicknesses into deposition samples with the same size; s3, the deposition samples are subjected to cutting sample preparation through a wire cut electric discharge machine; s4, testing the electrochemical corrosion performance of the deposition samples by using an electrochemical workstation; and S5, under an external voltage condition, measuring a dynamic potential polarization curve and an EIS curve of the deposition samples in a NaCl solution environment. The test conclusion obtained by the test method provided by the invention is as follows: the corrosion trend of fine WC / 316L is minimum, the corrosion rate is minimum, the inhibition effect on current is strongest, and the fine WC / 316L shows the best corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of laser melting deposition, and in particular to a method for testing the electrochemical corrosion performance of a coarse and fine WC reinforced 316L deposition sample. Background Art

[0002] The corrosion resistance of components is crucial in engineering applications and directly affects their service life and performance stability. In order to evaluate the corrosion resistance of deposited samples, electrochemical corrosion determination methods are usually used. The main evaluation parameters of electrochemical corrosion performance include the self-corrosion potential (Ecorr), self-corrosion current density (icorr), passivation current density (ip), passivation potential (Ep) and polarization resistance (Rp) obtained by the potentiodynamic polarization curve (Tafel) and electrochemical impedance spectroscopy (EIS). These parameters can not only reflect the corrosion resistance of the material, but also provide important information about the corrosion process and anti-corrosion mechanism. Summary of the invention

[0003] The object of the present invention is to provide a method for testing the electrochemical corrosion performance of coarse and fine WC reinforced 316L deposition samples to solve the above-mentioned defects caused by the prior art.

[0004] A method for testing the electrochemical corrosion performance of coarse and fine WC reinforced 316L deposition samples, comprising the following testing steps:

[0005] S1: 316L powder and WC powders of different particle sizes were uniformly mixed to obtain coarse and fine WC / 316L composite materials;

[0006] S2: Using laser melting deposition equipment, different types of coarse and fine WC / 316L composites were prepared into deposition samples of the same size;

[0007] S3: Use electric spark wire cutting machine to cut and prepare samples of these deposited samples;

[0008] S4: The electrochemical corrosion performance of these deposited samples was tested using an electrochemical workstation, and the measurement system was a three-electrode system;

[0009] S5: Under the condition of applied voltage, the dynamic potential polarization curves of these deposited samples in the NaCl solution environment are measured, and the corrosion current density (icorr), corrosion potential (Ecorr), polarization resistance (Rp), anode Tafel slope (βa) and cathode Tafel slope (βc) are obtained. The EIS curves of these deposited samples in the NaCl solution environment are also measured, and the capacitive reactance arc and impedance values ​​are obtained.

[0010] Preferably, four types of coarse and fine WC / 316L composite materials are included: ① 316L; ② coarse WC / 316L; ③ fine WC / 316L; ④ coarse WC+fine WC / 316L.

[0011] Preferably, before testing, the surfaces of the four deposited samples are immersed in a 3.5 wt. % NaCl solution for 1 hour to ensure a stable open circuit voltage.

[0012] Preferably, after the test, the electrochemical impedance spectroscopy is analyzed using ZSimpWin software, and a corresponding equivalent circuit is established.

[0013] Compared with the prior art, the present invention has the following advantages:

[0014] (1) The corrosion potentials of the four deposited samples in 3.5wt.% NaCl solution were -0.997V, -0.833V, -0.980, and -0.977V, respectively. The corrosion current density of fine WC / 316L (2.299μA / cm2) was about 12.66% of the corrosion current density of pure 316L (18.16μA / cm2). The maximum polarization resistance Rp of fine WC / 316L (15841.7Ω) was about 8.24 times that of pure 316L (1921.4Ω). Fine WC / 316L had the smallest corrosion tendency, the smallest corrosion rate, the strongest barrier to current, and exhibited the best corrosion resistance.

[0015] (2) The capacitive reactance arc radius of the fine WC / 316L deposited sample is the largest, followed by coarse WC+fine WC / 316L and coarse WC / 316L. The capacitive reactance arc radius of the 316L deposited sample is the smallest, indicating that the fine WC / 316L deposited sample is the most difficult to corrode, and the 316L deposited sample is the most susceptible to corrosion. The impedance modulus value |Z| of the fine WC / 316L deposited sample is the highest, and the phase angle is also the largest, which further indicates that its corrosion resistance is good.

[0016] (3) The total impedance values ​​of 316L, fine WC / 316L, coarse WC / 316L, and coarse WC+fine WC / 316L in 3.5wt.% NaCl solution are 132.34Ω, 208.32Ω, 59.12Ω, and 48.68Ω, respectively. The total impedance value of the fine WC / 316L deposited sample is the largest, indicating that a large amount of corrosion products are formed on its surface. The formed passivation film can increase the impedance value, greatly hindering the penetration of Cl ions in the NaCl solution into the fine WC / 316L deposited sample, thereby preventing the transfer of charge and effectively inhibiting the further progress of corrosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The figure is a flow chart of the electrochemical corrosion performance test of four deposited samples in the present invention.

[0018] Figure 2 The following are dynamic potential polarization curves of four deposited samples in the present invention in a 3.5 wt. % NaCl solution environment.

[0019] Figure 3 These are the EIS curves of the four deposition samples in the present invention.

[0020] Figure 4 Schematic diagram of the corrosion process of WC particle reinforced 316L in the present invention. DETAILED DESCRIPTION

[0021] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0022] like Figure 1 As shown, a method for testing the electrochemical corrosion performance of a coarse and fine WC-reinforced 316L deposition sample includes the following test steps:

[0023] S1: 316L powder and WC powders of different particle sizes were uniformly mixed to obtain coarse and fine WC / 316L composite materials;

[0024] S2: Using laser melting deposition equipment, different types of coarse and fine WC / 316L composites were prepared into deposition samples of the same size;

[0025] S3: Use electric spark wire cutting machine to cut and prepare samples of these deposited samples;

[0026] S4: The electrochemical corrosion performance of these deposited samples was tested using an electrochemical workstation, and the measurement system was a three-electrode system;

[0027] S5: Under the condition of applied voltage, the dynamic potential polarization curves of these deposited samples in the NaCl solution environment are measured, and the corrosion current density (icorr), corrosion potential (Ecorr), polarization resistance (Rp), anode Tafel slope (βa) and cathode Tafel slope (βc) are obtained. The EIS curves of these deposited samples in the NaCl solution environment are also measured, and the capacitive reactance arc and impedance values ​​are obtained.

[0028] In this embodiment, four kinds of coarse and fine WC / 316L composite materials are included: ① 316L; ② coarse WC / 316L; ③ fine WC / 316L; ④ coarse WC+fine WC / 316L.

[0029] In this embodiment, before testing, the surfaces of the four deposited samples were immersed in a 3.5 wt. % NaCl solution for 1 hour to ensure that a stable open circuit voltage was obtained.

[0030] In this embodiment, after the test, the electrochemical impedance spectroscopy was analyzed using ZSimpWin software, and a corresponding equivalent circuit was established.

[0031] like Figure 2 As shown, the potentiodynamic polarization curves of four deposited samples in a 3.5wt.% NaCl solution environment. It can be seen that in the anode area, as the corrosion voltage slowly increases, the corrosion current increases significantly, and the surface is in an active dissolution state. Comparing the characteristics of the four polarization curves, it can be seen that there is an obvious passivation behavior. When entering the passivation zone, the voltage gradually increases, and the corrosion current remains almost unchanged, indicating that the deposited layer is in a passivation state, because the oxide film generated by passivation inhibits its further dissolution, and the corrosion rate slows down. Because the electrolyte is a neutral solution, the electrolyte cannot react directly with the anode material. As the voltage slowly increases, the corrosion current also slowly increases, and the oxide film slowly dissolves. Through the analysis of the polarization curves, the values ​​of several key parameters are obtained, including corrosion current density (icorr), corrosion potential (Ecorr), polarization resistance (Rp), anode Tafel slope (βa) and cathode Tafel slope (βc). The specific values ​​are shown in Table 1. Corrosion potential (Ecorr) refers to the potential change trend of the material during the corrosion process. The more negative the value, the greater the corrosion trend. Corrosion current density (icorr) is a physical parameter that describes the corrosion rate. The larger the value, the faster the corrosion rate. Polarization resistance (Rp) represents the resistance of the electrode system to the current. The larger the value, the more obvious the resistance of the electrochemical system to the current, and the slower the corrosion rate of the electrode. The Tafel slope of the anode and cathode reflects the kinetic characteristics of the electrochemical reaction, which is crucial for understanding the electron transfer process in the corrosion process.

[0032] According to the data in Table 1, the corrosion potentials of the four deposited samples 316L, fine WC / 316L, coarse WC / 316L, (coarse WC+fine WC) / 316L in 3.5wt.% NaCl solution are -0.997V, -0.833V, -0.980, -0.977V respectively. The corrosion current density is 18.16μA / cm2, 2.299μA / cm2, 21.29μA / cm2, 11.08μA / cm2 respectively. The polarization resistance is 1921.4Ω, 15841.7Ω, 1701.4Ω, 3102.4Ω respectively. The maximum polarization resistance Rp (15841.7Ω) of fine WC / 316L is about 8.24 times that of pure 316LRp (1921.4Ω). Fine WC / 316L has the smallest corrosion tendency, the smallest corrosion rate, the strongest barrier to electric current, and exhibits the best corrosion resistance.

[0033] Table 1 Electrochemical corrosion parameters of four deposited samples

[0034]

[0035] The cathode slopes of the four deposition samples are all greater than the anode slopes, indicating that the reaction mainly occurs at the cathode. The reactions occurring at the anode are as follows:

[0036] Fe→Fe 2+ +e - (1)

[0037] Cr→Cr 3+ +3e - (2)

[0038] The generated Fe and Cr ions react with O dissolved in the NaCl solution. 2 The reaction occurs, resulting in the formation of a thin passive film on the surface of the deposited sample. This oxide film consists of two main parts, the outer thin layer is mainly composed of iron oxide, and the inner thicker layer is mainly composed of chromium oxide. The iron oxide layer is located on the outside of the oxide film and provides a small part of the corrosion resistance. The main corrosion protection comes from the inner chromium oxide layer. The mechanism of the formation of the passive film is as follows:

[0039]

[0040] However, as the polarization potential continues to increase, the dissolution rate of the passive film on the surface of the deposited sample is much greater than the formation rate, and the anodic activity of the dissolution process on the surface of the deposited sample is enhanced, so that the passive film will be quickly broken down and corrosion will continue.

[0041] In order to further study the electrochemical corrosion behavior of the four deposited samples, the EIS curves of the four deposited samples in 3.5wt.% NaCl solution were analyzed. Figure 3 As shown. The equivalent circuit diagram used for fitting is R(CR(QR)), as shown Figure 3 -d. Rs in the circuit diagram is the solution resistance, CPE1 is the constant phase element, Rct is the charge transfer resistance, Rf is the passivation film resistance, C is the passivation film capacitance, n is the dispersion index (0<n<1), and the relevant values ​​are shown in Table 2. The χ2 values ​​of 316L, fine WC / 316L, coarse WC / 316L, and coarse WC+fine WC / 316L are 9.08×10-4, 5.143×10-4, 1.394×10-3, and 1.127×10-3, respectively, indicating that the experimental data and the fitting data fit well, and the fitting data has reference significance.

[0042] Table 2 EIS curve fitting results

[0043]

[0044]

[0045] Figure 3 -a is the Nyquist curve of four deposited samples. Each of the four deposited samples corresponds to a capacitive arc. In the electrochemical corrosion reaction, the radius of the capacitive arc represents the electrochemical reaction resistance of the deposited sample. The larger the radius of the capacitive arc, the greater the electrochemical reaction resistance, and the more difficult it is for the corrosion reaction to occur. Figure 3 -a, it can be seen that the capacitive reactance arc radius of the fine WC / 316L deposited sample is the largest, followed by coarse WC+fine WC / 316L and coarse WC / 316L. The capacitive reactance arc radius of the 316L deposited sample is the smallest, indicating that the fine WC / 316L deposited sample is the most difficult to corrode, and the 316L deposited sample is the most susceptible to corrosion. Figure 3 -b and 3-c are Bode plots. The impedance modulus value |Z| of the fine WC / 316L deposited sample is the highest and the phase angle is also the largest, which further indicates that its corrosion resistance is better.

[0046] In the process of electrochemical corrosion, the larger the impedance value, the greater the obstruction to the charge transfer process, and the more difficult the corrosion. The total impedance value in the electrochemical corrosion system is the sum of the solution resistance Rs and the passivation film resistance Rf. The total impedance values ​​of 316L, fine WC / 316L, coarse WC / 316L, and coarse WC+fine WC / 316L in 3.5wt.% NaCl solution are 132.34Ω, 208.32Ω, 59.12Ω, and 48.68Ω, respectively. The total impedance value of the fine WC / 316L deposited sample is the largest, indicating that a large number of corrosion products are formed on its surface. The formed passivation film layer can increase the impedance value, greatly hindering the penetration of Cl ions in the NaCl solution to the fine WC / 316L deposited sample, thereby preventing the transfer of charge and effectively inhibiting the further progress of corrosion. Based on the above analysis, the fine WC / 316L deposited sample exhibits strong electrochemical corrosion resistance, which is consistent with the conclusion of the aforementioned potentiodynamic polarization curve.

[0047] According to the test results of the above electrochemical corrosion performance, the corrosion resistance of the four deposited samples in 3.5wt.% NaCl solution showed different trends, among which fine WC / 316L was the most corrosion resistant, followed by coarse WC+fine WC / 316L and coarse WC / 316L. The corrosion resistance of 316L was the worst. This is mainly because after adding WC particles to 316L, even if the passivation film is broken down, the WC particles can act as a physical barrier to prevent further corrosion, thereby improving the corrosion resistance. The schematic diagram of the surface corrosion passivation of WC particles reinforced 316L is shown in Figure 4 shown.

[0048] At the same mass fraction, the number of fine WC particles is larger, the surface area is larger, the more heat is absorbed, and the number of carbides produced after the WC particles are melted is also larger. Carbides can be regarded as hard phases, which can play a role in solid solution strengthening when distributed between dendrites. The more carbides there are, the more obvious the solid solution strengthening effect is. Among the four deposited samples, the number of carbides is from high to low: fine WC / 316L, coarse WC+fine WC / 316L, coarse WC / 316L, 316L, so the fine WC / 316L deposited sample has the best corrosion resistance.

[0049] Therefore, the embodiments disclosed above are only illustrative in all aspects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are included in the present invention.

Claims

1. A method for testing the electrochemical corrosion performance of coarse and fine WC reinforced 316L deposition samples, characterized in that: The test steps include: S1: 316L powder and WC powders of different particle sizes were uniformly mixed to obtain coarse and fine WC / 316L composite materials; S2: Using laser melting deposition equipment, different types of coarse and fine WC / 316L composites were prepared into deposition samples of the same size; S3: Use electric spark wire cutting machine to cut and prepare samples of these deposited samples; S4: The electrochemical corrosion performance of these deposited samples was tested using an electrochemical workstation, and the measurement system was a three-electrode system; S5: Under the condition of applied voltage, the dynamic potential polarization curves of these deposited samples in the NaCl solution environment are measured, and the corrosion current density (icorr), corrosion potential (Ecorr), polarization resistance (Rp), anode Tafel slope (βa) and cathode Tafel slope (βc) are obtained. The EIS curves of these deposited samples in the NaCl solution environment are also measured, and the capacitive reactance arc and impedance values ​​are obtained.

2. The electrochemical corrosion performance testing method of a coarse and fine WC reinforced 316L deposition sample according to claim 1 is characterized by: It includes four kinds of coarse and fine WC / 316L composite materials: ①316L; ②coarse WC / 316L; ③fine WC / 316L; ④coarse WC+fine WC / 316L.

3. The electrochemical corrosion performance testing method of a coarse and fine WC reinforced 316L deposition sample according to claim 2 is characterized in that: Before testing, the surfaces of the four deposited samples were immersed in a 3.5 wt. % NaCl solution for 1 hour to ensure a stable open circuit voltage.

4. The electrochemical corrosion performance testing method of a coarse and fine WC reinforced 316L deposition sample according to claim 1, characterized in that: After the test, the electrochemical impedance spectroscopy was analyzed using ZSimpWin software and the corresponding equivalent circuit was established.